2019
DOI: 10.1186/s12885-019-6133-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and risk association of polymorphisms in Aurora kinases A, B and C with genetic susceptibility to gastric cancer development

Abstract: Background Single nucleotide polymorphisms (SNPs) in genes encoding mitotic kinases could influence development and progression of gastric cancer (GC). Methods Case-control study of nine SNPs in mitotic genes was conducted using qPCR. The study included 116 GC patients and 203 controls. In silico analysis was performed to evaluate the effects of polymorphisms on transcription factors binding sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Accordingly, the absence of mutations in the FH-mutation–negative probands in our study may be attributable to nucleotide alterations in other genes, nucleotide variations in other parts of the APOB gene (not addressed in this study), or a combination of LDL-C-raising alleles. Be that as it may, previous studies on other diseases have demonstrated that the presence and combinations of some polymorphisms can render individuals more susceptible to disease ( Khajali and Khajali, 2014 ; Mesic et al, 2019 ; Pinheiro et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the absence of mutations in the FH-mutation–negative probands in our study may be attributable to nucleotide alterations in other genes, nucleotide variations in other parts of the APOB gene (not addressed in this study), or a combination of LDL-C-raising alleles. Be that as it may, previous studies on other diseases have demonstrated that the presence and combinations of some polymorphisms can render individuals more susceptible to disease ( Khajali and Khajali, 2014 ; Mesic et al, 2019 ; Pinheiro et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al found that an allele T in AURKA SNP rs2273535 and T in rs1047972 were correlated with a reduced early adverse reaction in cervical cancer patients who received pelvic radiotherapy, but this has nothing to do with the cancer itself 41 . In addition, Mesic et al suggested that AURKA rs1047922 polymorphisms may influence the development of gastric cancer 42 . Although AURKA SNP rs758099 is located in intron area, they also found that it could have an impact on gastric cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although, AURKA rs1047972 revealed negative results for altering CNS tumor risk, AURKA rs1047972 variants were identified to change lung adenocarcinoma (LADC) development probably [ 47 ]. Moreover, the rs1047972 variants were associated with elevated gastric cancer (GC) risk and basal-like breast cancer [ 48 , 49 ]. With no association of AURKA rs2273535 with CNS tumor susceptibility, AURKA rs2273535 polymorphisms were associated with overall enhanced cancer susceptibility, particularly breast cancer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%